2021
DOI: 10.3390/brainsci11091244
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bulbar Function in Adult Patients with 5q-SMA Type 2 and 3 under Treatment with Nusinersen

Abstract: The antisense oligonucleotide nusinersen has been shown to improve trunk and limb motor function in patients with spinal muscular atrophy (SMA). Bulbar dysfunction, which is regularly present in SMA, is not captured by standard motor scores, and validated measurement instruments to assess it have not yet been established. Data on whether and how bulbar function changes under gene-based therapies in adult SMA patients are also unavailable. Here, we present data on the course of bulbar dysfunction assessed prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Children and adults with SMA type 3 (Kugelberg-Welander disease) achieve the ability to walk independently during development and show sparse comorbidities such as scoliosis and respiratory muscle weakness of varying severity [ 2 ]. Bulbar motor dysfunction may be present in SMA type 2 and 3, while patients with SMA type 2 are more likely to be affected [ 4 ]. SMA type 4 represents the mildest form with late onset in adulthood, comprising less than 5% of all SMA cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adults with SMA type 3 (Kugelberg-Welander disease) achieve the ability to walk independently during development and show sparse comorbidities such as scoliosis and respiratory muscle weakness of varying severity [ 2 ]. Bulbar motor dysfunction may be present in SMA type 2 and 3, while patients with SMA type 2 are more likely to be affected [ 4 ]. SMA type 4 represents the mildest form with late onset in adulthood, comprising less than 5% of all SMA cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…New disease-modifying treatment options call for objective and sensitive methods to identify motor improvement in adult SMA patients. In recent years, the evaluation of bulbar function gained more attention and increasing interest in research [ 7 , 16 , 17 , 26 , 41 ]. Measuring small changes in adult SMA patients is complex and the combined use of several outcome measures is recommended—particularly so for specific subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…We used bulbar function items 1–3 of the Amyotrophic Lateral Sclerosis Functional Rating Scale Revised (b-ALSFRS-R) and the Sydney Swallow Questionnaire (SSQ) to assess bulbar function in this study, as published previously for patients treated with nusinersen [ 16 ]. Data were collected during regular follow-up of patients shortly before treatment initiation (T0) and at 4 months (T1) and 12 months (T2) after treatment initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Bulbar dysfunction typically occurs in the early and advanced disease stages, mostly in SMA types 1 and 2 [ 13 15 ]. In a previous study, we evaluated bulbar function in adults with SMA under nusinersen and found no improvement but preservation over 14 months of therapy [ 16 ]. For risdiplam, pivotal studies have shown preservation of swallowing function in SMA infants with sustained oral feeding ability over 12 months, indicating a relevant effect of risdiplam on bulbar function in this patient group [ 17 ].…”
Section: Introductionmentioning
confidence: 99%